URGENSI KEBERADAAN LEMBAGA PEMANTAU PEMILIHAN SEBAGAI PENGAWAL SUARA KOLOM KOSONG - Mooduto, Andika Muhammad Arifin; Huda, Uu Nurul (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
This study aims to examine and analyze the active participation of the people as the holder of the highest sovereignty in the implementation of the Regional Head Election (Pilkada) in order to run with justice, with full responsibility and avoid elements of violations. This study uses the juridical normative method with the consideration that the research undertaken seeks to determine the extent to which the reality of the application of a rule. The results of this study conclude that the arrangement regarding the Election Monitoring Institution (LPP) in the Pilkada seems to be positioned as mere informants without sufficient strength, besides that there is also a real condition that if the fate of the LPP is indeed in intersection, they are encouraged to stay alive but are only given a few resources, so that strengthening the LPP is an absolute prerequisite for realizing justice in Pilkada.